LITERATURE REVIEW: OFF LABEL USE ON , METFORMIN AS TREATMENT FOR POLYCYSTIC OVARY SYNDROME (PCOS) - Shabina Putri Alliya; Anggi Isnaini; Vian Saltiel Harefa; Dafni Aisyah Fariby; Najwa Adella Feriska; Falesya Jovanka Athallah; Anisa Puja Ningrum; Daniah Atikah; Primayanti Nurul Ilmi (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2025)
Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder affecting reproductive-aged women and is often accompanied by insulin resistance and hyperandrogenism. Metformin, a first-line antidiabetic agent, has been widely used in the treatment of PCOS due to its ability to improve insulin sensitivity, regulate menstrual cycles, reduce androgen levels, and promote ovulation. This literature review aims to critically evaluate and synthesize previous research findings on metformin and the influence of genetic and metabolic factors on individual responses in PCOS patients. Nine clinical studies published in the last five years were analyzed. The findings indicate that metformin consistently improves hormonal and metabolic parameters, particularly in overweight or insulin-resistant patients. Combination therapies, such as metformin with pioglitazone, liraglutide, or exenatide, were shown to be more effective than monotherapy in managing metabolic dysfunction and reproductive abnormalities. However, gastrointestinal side effects and interindividual variability in therapeutic response remain significant challenges. These results suggest that personalized treatment strategies based on patient phenotype and tolerance may optimize outcomes. Further research is needed to establish predictive markers and refine therapeutic regimens for long-term PCOS management.